The Career Consequences of Workplace Protest Participation: Theory and Evidence from the NFL “Take a Knee” Movement - Rheinhardt, Alexandra; Poskanzer, Ethan J.; Briscoe, Forrest (Organization Science, 2024)
Despite recognizing potential ramifications for employees who protest in the workplace, researchers rarely explore the career consequences that stem from such instances of workplace protest participation. We integrated research on employee activism, workplace deviance, and careers to theorize that workplace protest represents a perceived deviation from workplace norms that can influence an individual’s organizational and labor market mobility outcomes. We investigated this premise with the 2016 National Football League “take a knee” protests as a strategic research setting. The results indicate that protesting is associated with an increase in organizational exit although this effect is moderated by the degree to which the organization is sensitive to the underlying social movement (with an organization’s movement sensitivity operationalized with a four-part index composed of the team’s managers, personnel decision makers, owners, and customers). Protesting also is associated with labor market sorting across organizations as players who protest are more likely to make subsequent transitions to more movement-sensitive teams compared with players who do not protest. Overall, our findings offer contributions for research on employee activism, workplace deviance, and careers.